The Impact of Bio-Stimulants on Cd-Stressed Wheat (Triticum aestivum L.): Insights Into Growth, Chlorophyll Fluorescence, Cd Accumulation, and Osmolyte Regulation - Farhat, Fozia; Arfan, Muhammad; Wang, Xiukang; Tariq, Arneeb; Kamran, Muhammad; Tabassum, Hafiza Naila; Tariq, Ifra; Mora-Poblete, Freddy; Iqbal, Rashid; El-Sabrout, Ahmed M.; Elansary, Hosam O. (Frontiers in Plant Science, 2022)
It has been established that wheat (Triticum aestivum L.) has a higher Cd absorption capacity than other cereal crops causing an excess daily Cd intake and a huge threat for public health. Therefore, the reduction of Cd accumulation in wheat from the soil is a crucial food-security issue. A pot trial was performed on Cd-stressed wheat seedlings to evaluate the morphological and physio-biochemical responses via foliage spray of two different bio-stimulants, i.e., ascorbic acid (AsA) and moringa leaf extract (MLE). Two wheat cultivars (Fsd-08 and Glxy-13) were exposed to cadmium (CdCl2.5H2O) stress (0, 500, and 1,000 μM), along with foliar spray of AsA (0 and 50 mM) and MLE (0 and 3%). The most observable growth reduction was documented in plants that are exposed to a higher Cd concentration (1,000 μM), followed by the lower Cd level (500 μM). The wheat growth attributes, such as number of leaves per plant, number of tillers per plant, biomass yield, shoot/root length, and leaf area, were greatly depressed under the Cd stress, irrespective of the cultivar. Under the increasing Cd stress, a significant diminution was observed in maximum photochemical efficiency (Fv/Fm), photochemical quenching (qP), and electron transport rate (ETR) accompanied with reduced gas exchange attributes. However, Cd-induced phytotoxicity enhanced the non-photochemical quenching (NPQ) and internal carbon dioxide concentration (Ci), which was confirmed by their significant positive correlation with Cd contents in shoot and root tissues of both cultivars. The contents of proline, AsA, glycine betaine (GB), tocopherol, total free amino acid (TFAA), and total soluble sugar (TSS) were greatly decreased with Cd stress (1,000 μM), while MLE and AsA significantly enhanced the osmolytes accumulation under both Cd levels (especially 500 μM level). The Cd accumulation was predominantly found in the root as compared to shoots in both cultivars, which has declined after the application of MLE and AsA. Conclusively, MLE was found to be more effective to mitigate Cd-induced phytotoxicity up to 500 μM Cd concentration, compared with the AsA amendment.